Lattice thermal expansion of Pu1−yAmyO2−x plutonium–americium mixed oxides. Issue 6 (20th November 2017) - Vauchy, Romain; Joly, Alexis; Valot, Christophe
Abstract : The lattice thermal expansion of Pu1− y Am y O2− x mixed oxides was studied in situ in reconstituted air by high‐temperature X‐ray diffraction. The lattice parameter of the face‐centred cubic phase constituting the materials studied exhibited a more pronounced deviation from linearity as a function of both temperature and americium content in the mixed oxides. Abstract : Plutonium–americium mixed oxides, Pu1− y Am y O2− x, with various Am contents ( y = 0.018, 0.077, 0.21, 0.49, 0.80 and 1.00) were studied in situ by high‐temperature X‐ray diffraction. In this study, the lattice thermal expansion of the six compounds subjected to heat treatments up to 1773 K under reconstituted air (N2 + 21% O2 + ∼5 vpm H2 O) was investigated. The materials remained monophasic throughout the experiments and, depending upon the americium content, the lattice parameter of the face‐centred cubic phase deviated from linear lattice expansion at elevated temperatures as a result of the progressive reduction of Am 4+ to Am 3+ .